Digital Transformation and the 2030 Sustainable Development Agenda - Nirupam Bajpai; John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The Digital Revolution may not have made its way in any meaningful respect into the 2015 SDG Agenda, but over the past few years, it has become overwhelmingly clear that recent advances in digital technology will be core to realizing the possibility of sustainable development around the globe. These cutting-edge innovations have the potential to revolutionize the design of infrastructure and urban environments, lay the groundwork for equitable, quality health and education systems, and redefine how resources are consumed and distributed between ecosystems and human environments. But the Digital Revolution shows signs of high risk in addition to these high rewards. If poorly managed, this societal transformation could instead deepen inequality, harm the prosperity of the most vulnerable, and kneecap the cause of sustainable development for generations. These consequences are already becoming visible; while technological advances have allowed billions to continue their normal lives relatively undisturbed during the COVID-19 pandemic, they have also enabled the rise of an intransigent digital underclass in developed and developing economies alike without the protections afforded to more traditional workers.Understanding the theoretical linkages between digital technology and sustainable development is a simple task, but it is far more complicated to translate these insights into actionable policy which will further sustainability rather than hindering it. Some sustainable applications of digital technology are still undergoing research, while other approaches have been developed but wait on greater institutional backing to scale and thrive. Therefore, specific uses of digital technology which synergize with the SDG Agenda must be explicitly identified, outlined, and prioritized as destinations for key investments. Only by doing this can the new, transformative technological advances of the 21st century be leveraged to launch sustainable development into a new trajectory impossible under current Business-As-Usual practices.
Keywords: 330